Intervensi â€œProtect Meâ€ Sebagai Upaya Mengatasi Dan Mencegah Kekerasan Remaja Hamil - Eny Dewi Pamungkas; Setyowati Setyowati; Wiwit Kurniawati (Jurnal Keperawatan Padjadjaran, 2022)
Background: Some pregnant adolescents experience violence that has a negative impact for the pregnant adolescent itself and also their babies. It is necessary to make a health promotion intervention as an effort to prevent and control violence against pregnant adolescents.Purpose: This research aimed to analyse the influence of the health education about domestic violence named “Protect Me” on knowledge, selfefficacy, and help-seeking behavior again violence among adolescent with pregnancy.Methods: There were 37 participants of pregnant adolescents involved in violence screening. Based on the screening results, 30 participants experienced violence and agreed to involve in this research. Research with pre-experimental study design using a total sampling of 30 pregnant adolescents experiencing domestic violence from April to June 2020.Results: The results showed that 6.7% of pregnant adolescents experienced psychological, physical and economic violence and 13.3% pregnant adolescents experienced sexual violence. There was a significant difference between the level of knowledge (p < 0.001) and help-seeking behavior (p = 0.002) of pregnant adolescents after being given “Protect Me” intervention and Self-efficacy has no relation with Protect Me intervention (p = 0.186)Conclusion: The results of the research concluded that the domestic violence prevention and management efforts could be carried out by applying education based intervention “Protect Me”, to improve the knowledge and help-seeking behavior of pregnant adolescents.